2016
DOI: 10.1111/ajgw.12210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of berry diameter and colour on some determinants of wine composition ofVitis vinifera L. cv. Riesling

Abstract: Background and Aims To successfully use berry sorting in winemaking, it is crucial to understand the interaction of physical and chemical composition of berries. The aim of this study was to investigate the relationship between berry diameter and colour and aspects of wine composition, such as titratable acidity, aroma compounds and phenolic substances of Vitis vinifera L. cv. Riesling. Methods and Results In a first trial, berries were sorted into three berry diameter classes with equal TSS concentration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…Regarding the proportion of the different berry size groups Riesling showed the highest proportion for berry size groups 5 (12.5-14 mm) and 6 (14-16 mm), which was in accordance with previous literature [19]. In contrast, Cabernet Sauvignon berries were almost entirely in classes 4 (10-12.5 mm), 5 and 6.…”
Section: Bunch Structure Measuressupporting
confidence: 91%
See 4 more Smart Citations
“…Regarding the proportion of the different berry size groups Riesling showed the highest proportion for berry size groups 5 (12.5-14 mm) and 6 (14-16 mm), which was in accordance with previous literature [19]. In contrast, Cabernet Sauvignon berries were almost entirely in classes 4 (10-12.5 mm), 5 and 6.…”
Section: Bunch Structure Measuressupporting
confidence: 91%
“…So far, on white cultivars, only greenhouse experiments were conducted, showing that there was no eCO 2 effect on malic or tartaric acid at berry maturity [12,13]. Interestingly, a previous study on Riesling berry size [19] demonstrated that an increase in berry size was associated with increased malic acid concentration, which could account for a direct eCO 2 effect on berry size, and this in turn resulted in an enhancement of malic acid under eCO 2 . A similar achievement was made for Cabernet Sauvignon, resulting in higher malic acid and lower total acid concentration with increasing berry size classes [20].…”
Section: Berry Developmentmentioning
confidence: 98%
See 3 more Smart Citations